Constitutional equality law and the right to education : tackling poverty and class inequality through public interest law - Mitchell, Ben (Trinity College (Dublin, Ireland). School of Law, 2017)
This thesis is a study of the constitutional implications of inequality on the basis of poverty, social class and socio-economic status in the education system in Ireland. The core research question is whether the Constitution could protect a substantive conception of equality, and whether it could extend to poverty, social class and socio-economic status. The thesis then assesses whether activists could use litigation to provoke the political system to reform and equalise the provision of education. This involves a doctrinal assessment of what the law is and how it could develop, as well as a sociological and political assessment of the role of law.
Keywords: Law, Ph.D.; PhD Trinity College Dublin, 2017